On the advantages and disadvantages of virtual continuing medical education: a scoping review - Courtney Cheng; Janet Papadakos; Ben Umakanthan; Rouhi Fazelzad; Maria Athina (Tina) Martimianakis; Mohamed Ugas; Meredith Elena Giuliani (Canadian Medical Education Journal, 2023)
Introduction: With the COVID-19 pandemic, most continuing medical education activities became virtual (VCME). The authors conducted a scoping review to synthesize the advantages and disadvantages of VCME to establish the impact of this approach on inequities that physicians face along the intersections of gender, race, and location of practice.